2012
DOI: 10.1103/physrevlett.108.247212
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Heisenberg Behavior ofJeff=1/2Isospins in the Paramagnetic State of the Spin-Orbital Mott InsulatorSr2IrO

Abstract: Dynamical correlations of J eff = 1/2 isospins in the paramagnetic state of spin-orbital Mott insulator Sr2IrO4 was revealed by resonant magnetic x-ray diffuse scattering. We found two-dimensional antiferromagnetic fluctuation with a large in-plane correlation length exceeding 100 lattice spacings at even 20 K above the mangnetic ordering temperature. In marked contrast to the naive expectation of strong magnetic anisotropy associated with an enhanced spin-orbit coupling, we discovered isotropic isospin correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
175
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 21 publications
(33 reference statements)
22
175
3
Order By: Relevance
“…The former surprisingly indicates that a system with very strong spin-orbit coupling can mimic a system without it. Experimentally, it has been confirmed that the canted antiferromagnetic structure of Sr 2 IrO 4 derives from a predominantly isotropic nearest-neighbor magnetic exchange coupling [8][9][10] . Thus, Sr 2 IrO 4 becomes the first non-cuprate material to realize a (iso)spin-1/2 Heisenberg antiferromagnet in a quasitwo-dimensional square lattice-a possible platform for high temperature superconductivity [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The former surprisingly indicates that a system with very strong spin-orbit coupling can mimic a system without it. Experimentally, it has been confirmed that the canted antiferromagnetic structure of Sr 2 IrO 4 derives from a predominantly isotropic nearest-neighbor magnetic exchange coupling [8][9][10] . Thus, Sr 2 IrO 4 becomes the first non-cuprate material to realize a (iso)spin-1/2 Heisenberg antiferromagnet in a quasitwo-dimensional square lattice-a possible platform for high temperature superconductivity [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…23 Some papers indicate the ordered moment can be produced via slight canting of the otherwise AF moments. [24][25][26][27] The canting angle (see Fig. 1b) occurs due to the deviation of the Ir-O-Ir angle from 180 • via Dzyaloshinskii-Moriya interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the recent discovery of a new pseudospin-1/2 Heisenberg AF on a square lattice, Sr 2 IrO 4 (refs [13][14][15][16][17][18], we demonstrate a novel experimental approach using resonant inelastic X-ray scattering (RIXS), which is a rapidly evolving tool especially well suited for such 5d transition-metal oxides, to address this longstanding problem. On the basis of its remarkable similarity to superconducting cuprates in structural 18 , electronic 13 and magnetic aspects [14][15][16] , superconductivity has been predicted in Sr 2 IrO 4 (ref.…”
mentioning
confidence: 99%